2021
DOI: 10.22207/jpam.15.4.60
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Rotavirus in Mollusks from the Oued El Maleh Estuary of Mohammedia, Morocco

Abstract: Viral outbreaks can result from the consumption of contaminated bivalve mollusks. However, despite the regulation related to enteric bacteria in food products, the consumption of raw and undercooked mollusks remains linked to viral epidemics in human populations. Real-time RT-PCR is a highly sensitive approach for detecting and quantifying enteric viruses, and after eliminating enzymatic amplification inhibitors from samples of interest, sensitive and specific tests, like real-time RT-PCR, can facilitate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…RVA was the third most detected virus, with similar or higher detection rates reported in shellfish from Italy, Argentina, Morocco and Japan, ranging from 12.9% to 57.8% [78,[88][89][90]. Compared to our results, other studies detected RVA less frequently in bivalve samples (varying from 0% to 8.3%) in Brazil, Thailand, Italy, South Korea and Singapore [15,18,21,66,74,91].…”
Section: Discussionsupporting
confidence: 81%
“…RVA was the third most detected virus, with similar or higher detection rates reported in shellfish from Italy, Argentina, Morocco and Japan, ranging from 12.9% to 57.8% [78,[88][89][90]. Compared to our results, other studies detected RVA less frequently in bivalve samples (varying from 0% to 8.3%) in Brazil, Thailand, Italy, South Korea and Singapore [15,18,21,66,74,91].…”
Section: Discussionsupporting
confidence: 81%
“…Shellfish are known to accumulate human pathogens, such as human enteric viruses (e.g., rotavirus in mussels [ 52 , 53 ], enterovirus [ 32 , 54 ], HAV [ 26 , 55 ], and norovirus [ 27 , 56 , 57 ] in oysters).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies reported HEV presence in mussels grown naturally in wild areas and commercially available in Scotland [ 28 ], Spain [ 7 , 67 , 68 ], and Italy [ 4 , 69 ]. Similarly, there is evidence that HEV is circulating in the Moroccan population [ 70 ]. The absence of detection at Cherrat estuary is explained by the number of HEV particles discharged in the environment is too low to be detected or the virus may have a very short period of persistence in human waste.…”
Section: Discussionmentioning
confidence: 99%
“…Detected samples Average Ct 10 4 3/3 23.5 10 4), the aim of which was to assess the prevalence of RVA in mussel specimens collected from the Oued El Maleh estuary, revealed the presence of rotavirus RNA in 37.5% of the batches of samples analyzed, this allows us to distinguish that this virus is already in circulation in Morocco.…”
Section: Nb Of Rna Copies Per Reactionmentioning
confidence: 99%
“…The consumption of shellfish products, although recommended for their nutritional value, may pose a risk to human health due to their filtering activity and ability to bioaccumulation pathogens from surrounding waters (3). Among other pathogens, human rotaviruses are excreted through the feces of infected individuals and can enter coastal areas through inefficient wastewater treatment, or direct discharge of untreated wastewater (4,5). This factor is of particular concern in developing countries, where untreated sewage is discharged into water sources, causing environmental pollution (6).…”
Section: Introductionmentioning
confidence: 99%